Muscle development of livestock animals: physiology, genetics and meat quality - Pas, M. F. W. te; Everts, M. E.; Everts, M. E.; Haagsman, H. P.; Haagsman, H. P.; Pas, M. F. W. te (Wallingford :CABI Publishing, 2004)
This book describes the development, growth and adaptation of livestock muscle tissue and contains 18 chapters divided into physiology, genetics and meat quality sections. The physiology section contains chapters on the mechanism of muscle fibre development in the fetus and the importance of high muscle fibre numbers for muscle mass and meat quality (1); muscle fibre type identification and characterization in livestock (2); manipulation of muscle fibre number during prenatal development (3); the effect of growth and exercise on muscle characteristics in relation to meat quality (4); implications of nutrition, hormone receptor expression and gene interactions for muscle development and disease (5); the impact of minerals and micronutrients on growth control (6); significance of exercise and thyroid hormones for development and performance (7); local and systemic regulation of muscle growth (8) and proteolytic systems and regulation of muscle remodelling and breakdown (9). The genetics section contains chapters on the muscle regulatory factors gene family in relation to meat production (10); the muscle transcriptome (11); genome analysis of quantitative trait loci for muscle tissue development and meat quality (12); functional genomics and proteomics in relation to muscle tissue (13); role of myostatin in muscle growth (14) and the genetics, physiology and meat quality aspects of the Callipyge mutation for sheep muscular hypertrophy (15). The meat quality section contains chapters on the genetic control of intramuscular fat accretion (16); postmortem muscle proteolysis and meat tenderness (17) and the water holding capacity of meat (18). Each chapter ends with a list of references and an index is located at the end of the book. This book will be of value for those interested in skeletal muscle biology and meat quality.
Keywords: LL120 - Meat Producing Animals; LL240 - Animal Genetics and Breeding, (New March 2000); LL250 - Animal Reproduction and Embryology, (New March 2000); LL500 - Animal Nutrition (General); LL600 - Animal Physiology and Biochemistry (Excluding Nutrition); QQ030 - Meat Produce; QQ500 - Food Composition and Quality; ZZ360 - Molecular Biology and Molecular Genetics, (Discontinued March 2000, Reinstated and Revised June 2002)